Validation of close‐kin mark–recapture (CKMR) methods for estimating population abundance. Issue 9 (16th July 2019) - Ruzzante, Daniel E.; McCracken, Gregory R.; Førland, Brage; MacMillan, John; Notte, Daniela; Buhariwalla, Colin; Mills Flemming, Joanna; Skaug, Hans
Abstract: Knowing how many individuals there are in a population is a fundamental problem in the management and conservation of freshwater and marine fish. We compare abundance estimates (census size, Nc ) in seven brook trout Salvelinus fontinalis populations using standard mark–recapture (MR) and the close‐kin mark–recapture (CKMR) method. Our purpose is to validate CKMR as a method for estimating population size. Close‐kin mark–recapture is based on the principle that an individual's genotype can be considered a "recapture" of the genotypes of each of its parents. Assuming offspring and parents are sampled independently, the number of parent–offspring pairs (POPs) genetically identified in these samples can be used to estimate abundance. We genotyped (33 microsatellites) and aged c. 2, 400 brook trout individuals collected over 5 consecutive years (2014–2018). We provide an alternative interpretation of CKMR in terms of the Lincoln–Petersen estimator in which the parents are considered as tagging the offspring rather than the offspring "recapturing" the parents. Despite various sources of uncertainty, we find close agreement between standard MR abundance estimates obtained through double‐pass electrofishing and CKMR estimates, which require information on age‐specific fecundity, and population‐ and age‐specific survival rates. Population sizes ( N ^ ) are estimated to range between 300 and 6, 000 adult individuals. Our study constitutes the first in situ validation of CKMR and establishes it as a useful method for estimating population size in aquatic systems where assumptions of random sampling and thorough mixing of individuals can be met.